Epidemiology of Brucellosis in Small Ruminants of Rural and Peri-Urban Areas of Multan, Pakistan - Mian Muhammad Awais; Bakhtawar Khadim; Masood Akhtar; Muhammad Irfan Anwar; Gohar Khadim; Abdul Sammad Ali Khan Shirwany; Halil Selcuk Biricik; Abdul Razzaq; Muhammad Sibtain Bhatti (Canadian Journal of Infectious Diseases and Medical Microbiology)
Brucellosis is a widespread zoonotic disease of veterinary and public health importance with considerably higher prevalence in developing/underdeveloped countries. This study reports the prevalence and risk determinants of brucellosis in small ruminants of peri-urban and rural areas of district Multan, Southern Punjab, Pakistan. For this purpose, sera samples (n = 392) of small ruminants were collected and subjected to preliminary screening using commercially available RBPT reagents followed by serodetection of brucellosis using multispecies i-ELISA kit (ID.vet, France). All the ELISA positive samples were confirmed by PCR using genus-specific primers, and frequencies of Brucella species in positive samples were enumerated using species-specific primers. Results indicated seropositivity rates of 9.69, 9.95, and 10.20% in study population using RBPT reagents of IDEXX-USA, ID.Vet-France, and VRI-Pakistan, respectively, with a statistically nonsignificant difference p>0.05. Results of ELISA showed an overall seroprevalence rate of 7.14% in target population with a slightly higher rate in sheep (7.65%) as compared to goat (6.63%) population (p=0.695; OR = 1.16, 95% CI = 0.53, 2.57). Results revealed that out of total positive samples, B. abortus was detected in 60.71% of seropositive samples and B. melitensis was detected in 14.28% of positive samples. It was revealed that risk factors including body condition scores, hygienic conditions of the housing facility, farming system, reproductive disorders, educational status of farmers, and awareness of farmers about brucellosis had significant association with brucellosis in small ruminants of study area p<0.05. Conversely, farm/herd size, locality, gender, age, weight, and parity showed a nonsignificant association p>0.05 with brucellosis. In conclusion, brucellosis is prevalent in small ruminants of Multan, Pakistan. It is recommended to devise and implement effective control strategies with a major focus on raising awareness about brucellosis in farmers for the containment of infection in the region.